Contextual and Graphic Characteristics of the Constitutional Verses in the Holy Qur’an and the Facts of the Language in them- A study of Selected Qur’anic Models- (Islamic Sciences Journal, 2023)
ABSTRACT                             The topic of our research deals with the study of selected models of constitutional verses in the Holy Qur’an and the statement of the relationship between them and the language, with an indication of the use of vocabulary within the Qur’anic context through the study of contextual and graphic phenomena in them.  Our work was limited to dividing the verses into constitutional principles, which we analyzed linguistically, focusing on the contextual and graphic characteristics of the texts with With an explanation of the impact of language in directing rulings, with an explanation of the reason for which the Holy Qur’an used a particular Vocabulary rather than another one within the context of the texts of the constitutional verses.
Keywords: Shura, verses, justice, constitutionality, provisions.